2022
DOI: 10.3389/fenvs.2022.1071668
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the performance of different thermal indices on quantifying outdoor thermal sensation in humid subtropical residential areas of China

Abstract: Considerations of urban microclimate and thermal comfort are necessary for urban development, and a set of guidelines for a comfortable microclimate must be developed. However, to develop such guidelines, the predictive ability of thermal indices for outdoor thermal perceptions under different design decisions must be defined. The present study aimed to determine suitable indices for assessing outdoor thermal reaction in humid subtropical residential areas of China. Five criteria of coefficients of determinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Zare, et al [57] classified the thermal sensation based on UTCI temperature (Table 4). Li, et al [58] stated that the UTCI was the most successful index that reasonably approximated the observed data in their study of a subtropical climate. In addition, Ghani, et al [59] reported average differences of 14% between the simulated and observed data in their investigation, which increases its creditability for use as the selected index in this study.…”
Section: Data Analysis Protocolmentioning
confidence: 72%
“…Zare, et al [57] classified the thermal sensation based on UTCI temperature (Table 4). Li, et al [58] stated that the UTCI was the most successful index that reasonably approximated the observed data in their study of a subtropical climate. In addition, Ghani, et al [59] reported average differences of 14% between the simulated and observed data in their investigation, which increases its creditability for use as the selected index in this study.…”
Section: Data Analysis Protocolmentioning
confidence: 72%
“…NET and UTCI were superior than PET in representing thermal perception of pedestrians in the Mediterranean climate (Pantavou et al 2013 ). In a similar study in a humid subtropical climate, UTCI was also found better than PET in quantifying thermal response outdoors (Li et al 2022 ) and determining the neutral temperature (Wei et al 2022 ). Considering heat stress, WBGT showed substantially poorer effectiveness than PET and UTCI in health risk assessment for marathon runners (Thorsson et al 2021 ), with PET showing the best applicability.…”
Section: Discussionmentioning
confidence: 98%
“…Atmosphere 2024, 15, x FOR PEER REVIEW 4 of 20 [20,21,25,26], measurements were carried out in different seasons. In this study, experimental measurements were carried out on different days in the summer season in order to obtain the heat stress indices [4] such as UTCI [18,19,21,34,[39][40][41][42][43], PET and mPET [32,33,[40][41][42][43], SET [37,38,40,41,43] and WBGT [34][35][36]41] for the assessment of temporal and cumulative outdoor thermal comfort. Furthermore, the heat stress exposure (HSE) metric [50] was also evaluated using UTCI, as in [50], and using the other indices as well.…”
Section: Study Areamentioning
confidence: 99%
“…A common method used by researchers to assess thermal comfort is by analyzing the indices of thermal stress experienced by people. In [4], Ren indicated that of the 100 manuscripts reviewed, the most commonly used thermal comfort indices were PET (43), UTCI (14), WBGT (12) and SET (7). Mayer [32] was one of the first researchers to use the PET index to assess thermal comfort in outdoor environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation